MATHS...PLEASE HELP

posted by .

what do you get when you:

integrate 10sin^4xcosx dx

when you integrate 9x^2e^6x^3 dx

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. calculus help please

    dy/dx = 2y^2 Integrating...y=2/3 y^3 + C put 1,-1 into the equation, and solve for C. Then find the y for x=2 if y= a^uhttp://math2.org/math/integrals/tableof.htm see exponential functions. dy/dx=2y^2 and if y=-1 when x=1, then when …
  2. Integral calculus

    Please do help solve the followings 1) Integrate e^4 dx 2) Integrate dx/sqrt(90^2-4x^2) 3) Integrate (e^x+x)^2(e^x+1) dx 4) Integrate xe^x2 dx e^4 is a constant. 3) let u= e^x + x du= (e^x + 1)dx 4) let u= x du=dx v= e^x dv= e^x dx
  3. calculus

    1) Integrate Cos^n(x) dx 2) Integrate e^(ax)Sinbx dx 3) Integrate (5xCos3x) dx I Will be happy to critique your thinking on these. 1) Derive a recursive relation. 2) Simplest by replacing sin(bx) by Exp[i b x] and taking imaginary …
  4. integrate

    integrate du/3u and integrate x/x^2 dx it might be simple...i just need a head start...tnx
  5. Calculus AB

    Please help me integrate this equation using partial fractions: Integrate [(x^2+5)/(x^3-x^2+x+3)]dx. Thank you very much.
  6. Calculus

    6.] Replace the integral in exercise 5 (int. (1/ 1 – t) dt a = 0, b = 1/2with ?
  7. calculus 2

    Justify, with a written explanation or a mathematical reasoning and with a sketch of at least two different cases, the following properties of integrals: a) If f(x) is less than or equal to g(x) for a<=x<=b then integrate from …
  8. Calc 1

    integrate from 0 to pi/4 (sec^2x)/((1+7tanx)^2)^1/3 integrate form pi^2/36 to pi^2/4 (cos(x^1/2))/(xsin(x^1/2))^1/2 integrate from 0 to pi/3 (tanx)/(2secx)^1/2
  9. maths

    integrate by parts integrate (4+x^2)^1/2
  10. Mathematics-Integration

    Question: Prove that [integrate {x*sin2x*sin[π/2*cos x]} dx] /(2x-π) } from (0-π) = [ integrate {sin x*cos x*sin[π/2*cos x} dx ] from (0-π). My thoughts on the question: We know that integrate f(x) dx from (0-a) = integrate f(a-x) …

More Similar Questions